RECURSOS DO BIM APLICADOS AO PROJETO DE ARQUITETURA PARA VERIFICAÇÃO DE REQUISITOS DA ABNT NBR 15575 - Silva Júnior, Mauro Augusto; Mitidieri Filho, Cláudio Vicente (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The purpose of this paper is to propose a way to incorporate the verification of performance criteria into architectural desings using Building Information Modeling (BIM), as an alternative to the two-dimensional design method traditionally used. The method based on constructive research was adopted for the development of this paper in the Master's Program. Requirements and Performance Criteria in Standard Brazilian Code ABNT NBR 15575:2013 "Edificações Habitacionais - Desempenho", were applied to the BIM model, in the development of architectural designs, so that the designer can make a verification throughout the development of the design. The result was promising considering the possibility of identifying and detailing approximately one third of the criteria in ABNT NBR 15575:2013, using only the modeling tool. Advantages have been identified in using modeling software features, such as tags and schedules for rules and requirements applications, which can be easily ascertained by the model. In this way, it is noted that this new process may result in better desings, with more complete and reliable performance information. If simulation tools are adopted and associated with architectural designs, other requirements and criteria checks may be made, such as simulation of thermal performance.